Material skills : evolution of materials. - Zijlstra, Els, ....- (Rotterdam : Materia, 2005)
The book "Material Skills, evolution of materials" describes the evolution of materials in terms of their historical development and presents a vision of the future. It assists designers to become aware of their inheritance and inspires them to use new materials in their work. Presented are around 100 unique, new and inspiring materials and projects which have been realised in a special way.
Accompanying the exhibition Material Skills. This exhibition will travel around the world during 2005 and 2006 and will be shown at Architecture Biennales, architectural fairs, museums of architecture and design and schools of architecture.
Infosteel
Keywords: Building materials -- Technological innovations; Materialen